2009
DOI: 10.1111/j.1471-0528.2009.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female genital mutilation on birth outcomes in Switzerland

Abstract: Objective The primary aim of this study was to determine the desires and wishes of pregnant patients vis-à-vis their external genital anatomy after female genital mutilation (FGM) in the context of antenatal care and delivery in a teaching hospital setting in Switzerland. Our secondary aim was to determine whether women with FGM and non-mutilated women have different fetal and maternal outcomes.Design A retrospective case-control study.Setting A teaching hospital.Population One hundred and twenty-two patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Issues in service delivery that hamper an adequate care for women with FGM, have been documented in other studies. These barriers in care include a lack of knowledge, communication problems, personal emotions and feelings of health professionals and the lack of technical guidance on clinical management (Nienhuis and Haaijer, 1995;Chalmers and Hashi, 2000;Widmark et al, 2002;Powell et al, 2004;Thierfelder et al, 2005;Leye et al, 2006;Wuest et al, 2009;Paliwal et al, 2013;Zenner et al, 2013). Our study showed that the provision of care in Flanders, by midwives, is hampered by a lack of knowledge on FGM, language barriers and difficulties in discussing this sensitive and complex issue with the women and her environment.…”
Section: Prevention Of Fgm and Provision Of Care For Women With Fgm Bmentioning
confidence: 64%
“…Issues in service delivery that hamper an adequate care for women with FGM, have been documented in other studies. These barriers in care include a lack of knowledge, communication problems, personal emotions and feelings of health professionals and the lack of technical guidance on clinical management (Nienhuis and Haaijer, 1995;Chalmers and Hashi, 2000;Widmark et al, 2002;Powell et al, 2004;Thierfelder et al, 2005;Leye et al, 2006;Wuest et al, 2009;Paliwal et al, 2013;Zenner et al, 2013). Our study showed that the provision of care in Flanders, by midwives, is hampered by a lack of knowledge on FGM, language barriers and difficulties in discussing this sensitive and complex issue with the women and her environment.…”
Section: Prevention Of Fgm and Provision Of Care For Women With Fgm Bmentioning
confidence: 64%
“…After sorting eligible studies according to outcomes, we included 44 primary publications reporting on obstetric outcomes: 21 comparative studies [1420, 28–47], 7 single group cross-sectional studies [48–54], 5 case series [6, 55–58], and 4 case reports [59–62]. …”
Section: Resultsmentioning
confidence: 99%
“…However, in the WHO report, it is concluded that “the serious obstetric consequences of FGM, when it is performed prior to the index pregnancy, are mainly due to the scarring resulting from FGM” [10, page 12]. In fact, a range of studies suggests that the most plausible pathway of effect between FGM/C and obstetric harm is inelastic scar tissue [1420]. However, divergent results among such studies and statements by scholars, physicians, and policy experts claiming that “reproductive health and medical complications associated with female genital surgeries in Africa are infrequent events” [21, page 22] have called into question whether FGM/C is associated with obstetric consequences for women.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 28 studies included in our original review [79, 18–41], we classified seven as prospective [7, 19, 22, 23, 28, 31, 40]. In these studies, exposure data were gathered from female study participants during an antepartum examination, followed by an assessment of outcome data during the delivery situation.…”
Section: Resultsmentioning
confidence: 99%